PENGARUH MINAT BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 22 SINJAI - Suci Auli Asri; Thamrin Tayeb; Mardiah Mardiah; St Ibrah Mustafa Kamal; Ida Suaidah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to determine: (1) a description of the students' interest in learning mathematics at SMPN 22 Sinjai, (2) a description of the motivation to learn mathematics of students at SMPN 22 Sinjai, (3) a description of the mathematics learning achievement of students of SMPN 22 Sinjai.The type of research used is quantitative with the ex post facto method. The sample in this study is the entire population, namely 60 students. The results showed that the students' interest in learning mathematics at SMPN 22 Sinjai was in the medium category. Students' motivation to learn mathematics is in the medium category. Students' mathematics learning achievement is in the medium category. There is a positive relationship between interest in learning and mathematics learning achievement of students at SMPN 22 Sinjai.. There is a positive relationship between learning motivation and student mathematics achievement. Learning interest and learning motivation simultaneously or collectively have a positive relationship to variable Y or learning achievement. That is, the higher the interest in learning and student motivation to learn together, the student achievement will increase, and vice versa.